Experiments on a delta wing using leading edge blowing to remove the secondary separation - Alexander, A. J. (College of Aeronautics, 1963)
It is found that the entrainment effect of a thin jet emerging from the leading edge of a delta wing is sufficient to remove the secondary separation. The minimum jet momentum required is small, but increases with incidence. Tests made without blowing, and with minimal blowing, include balance measurements, pressure plotting and tuft studies, over the range of incidence α = 0[degrees] - 20[degrees] . It is concluded that the presence of the secondary separation does not affect the lift or the vortex height appreciably, but is at least partly responsible for the large discrepancy between theory and experiment with regard to the spanwise position of the vortex.